حقوق المواطنة وواجباتها بين المواطن والدولة "رؤية سوسيولوجية" - "Citizenship rights and duties between the citizen and the state "Sociological vision - مكاوي, عشور (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
تعتبر المواطنة من المواضيع المهمة، والمتجددة التي شغلت تفكير الكثير من الباحثين، وما زالت إلى يومنا هذا؛ كل حسب التوجه والتخصص، والدوافع البحثية من حيث البنية المفاهيمية، والآليات التطبيقية، بالإضافة إلى السلوكيات المظهرية، فضمن دراستنا البحثية تم معالجتها من خلال مدخل الحق والواجب، والتي تهدف إلى الكشف عن المنطلقات التنظيرية، والممارسات الواقعية للمواطنة من خلال رؤية ثنائية بين المواطن، والدولة ضمن سياق النصوص القانونية المهيكلة لها على مستوى الدولة نفسها، بالإضافة إلى جملة الاتفاقيات والمعاهدات الدولية. Citizenship is an important and renewed topic that has occupied the thinking of many researchers and continues to this day; Each according to the orientation, specialization, and research motives in terms of the conceptual structure and application mechanisms, in addition to the phenotypic behaviors. Within our research studies, they were addressed through the entrance of right and duty, which aims to reveal theoretical perspectives and real practices of citizenship through a binary view between the citizen and the state within The context of the legal texts structured thereof at the state level itself, in addition to the totality of international agreements and treaties